LC-MS Analysis of Kigelia Pinnata (JACQ) DC. Root Bark- A Multi-Potent Medicinal Plant (AYUSHDHARA, 2023)
Phytochemicals of the plants have significant role in drug development for treatment of human diseases. Majority population in Africa, Asia and Latin America use plant based medicines. Kigelia pinnata DC. is a reputed African folklore drug and now abundantly found throughout India. It belongs to the family Bignoniaceae and used in different disease conditions traditionally. Out of various parts used, root bark owns medicinal properties like gynaecological complaints for fibroid, cancer of uterus and also reported biological activities such as antimalarial activity, antiprotozoal activity, antioxidant activity etc. The study was carried out for detailed exploration of biological active components in root bark extract of K. pinnata through Liquid chromatography/Mass Spectroscopy (LC/MS). It was performed on ESI ionization mode using both polarities. Total 63 known compounds are found from positive and negative mode. The molecules are derived from class group as terpenoid, flavonoids, phenols, glycoside and others which possess antioxidant, anti-inflammatory, antimicrobial, antihypertensive, anti-diabetic type of biological activities. This work therefore uncovers the phytochemical profile of K.pinnata root bark emphasizing their medicinal properties against important human diseases.